Effects of rice husk biochar and raised bed on CO2 flux and shallot (Allium cepa L.) production on peatland - Eka Widiawati Wijaya Kusuma; Azwar Maas; Sri Nuryani Hidayah Utami; Eni Maftuah (Universitas Sebelas Maret, 2021)
This study aims to assess the effect of rice husk biochar, raised beds, and chicken manure on the CO2 flux and shallot production on peatland. This study adopted a factorial randomized block design with three factors and three replications. The P1 treatment was recommended by the Swamp Land Agricultural Research Institute by adding chicken manure (5 ton ha−1) and rice husk biochar (5 ton ha−1) while the P2 treatment was recommended by the Vegetable Research Institute by adding chicken manure (10 ton ha−1). The raised beds heights were 20 cm (A) and 30 cm (B). Variance analyses were applied to each observation variable and followed by Duncan's Multiple Range Test at a 5% level. The P1A treatment was the best in improving the shallot production up to 10.88 tons and producing the lowest CO2 cumulative flux up to 0.158 ton ha-1 season-1.